FUZZY LOGIC CONTROL OF FLOTATION COLUMN - MAZLAN, MOHAMAD HAFEZ (IRC, 2017)
This project is conducted to deal with the advance control systems in order to stimulate a flotation dynamic control system which can adapt with the system that has changing behavior over period of time. In this project, MATLAB software has been used as the medium to perform modeling, simulation and identification on the stability of the designed control loops. The basic knowledge of control process must be applied in this project. Besides, this project also aims on better understanding of flotation process and working principle of flotation column. Flotation process is a process where hydrophobic particles are separated selectively from hydrophilic gangue in flotation column. In addition, results obtained from this project can be used as the guidelines and references for further improvement for controlling the percentage of level in flotation column in mining industry in the future study.